CircGSAP regulates the cell cycle of pulmonary microvascular endothelial cells via the miR-942-5p sponge in pulmonary hypertension - Sun, Yuanyuan; Wu, Wenhui; Zhao, Qinhua; Jiang, Rong; Li, Jinling; Wang, Lan; Xia, Shijin; Liu, Mingjie; Gong, Sugang; Liu, Jinming; Yuan, Ping (Frontiers in Cell and Developmental Biology, 2022)
Background: We recently demonstrated that circGSAP was diminished in lung tissues from patients with pulmonary arterial hypertension and in hypoxia-induced pulmonary microvascular endothelial cells (PMECs). However, the underlying role of circGSAP in PMECs remains unknown. The study aimed to investigate the contribution of circGSAP to proliferation, apoptosis and cell cycle of PMECs in hypoxic environment and explore the mechanism. Methods: The expression of circGSAP was quantified by real-time PCR or immunofluorescence in human lung tissue and PMECs. CircGSAP plasmid, circGSAP small interfering RNA (siRNA), miRNA inhibitor and target gene siRNA were synthesized to verify the role of circGSAP on regulating the proliferation, apoptosis, and cell cycle of PMECs. Results: CircGSAP levels were decreased in lungs and plasma of patients with pulmonary hypertension second to chronic obstructive pulmonary disease (COPD-PH) and were associated with poor outcomes of COPD-PH patients. Upregulation of circGSAP inhibited proliferation, apoptosis resistance and G1/S transition of PMECs. Dual luciferase reporter assays showed that circGSAP acted as a competitive endogenous RNA regulating miR-942-5p, and identified SMAD4 as a target gene of miR-942-5p, Then, we verified the functions of miR-942-5p and SMAD4 in PMECs. In addition, the effect of circGSAP siRNA on PMECs was mitigated by transfection of miR-942-5p inhibitor, and the effect of miR-942-5p inhibitor on PMECs was inhibited by SMAD4 siRNA. Conclusions: Our findings demonstrated that diminished circGSAP accelerated cell cycle to facilitate cell proliferation and apoptosis resistance through competitively binding miR-942-5p to modulate SMAD4 expressions in PMECs, indicating potential therapeutic strategies for COPD-PH.